The Rare Plants in The Alas Kedaton Tourism Forest, Tabanan, Bali - Wijana, Nyoman; Riawan, I Made Oka; Mulyadiharja, Sanusi (Advances in Tropical Biodiversity and Environmental Sciences, 2021)
Forests are a source of foreign exchange that has been exploited on a large scale for timber. This exploitation causes a rapid reduction in forest area. Until now, the destruction of the forest environment is still happening, both by illegal logging and illegal mining. This study aims to determine the number of rare plant species in Alas Kedaton Tourism Forest, Tabanan, Bali, Indonesia; and the factors causing the rarity of these plant species. The population in this research is the plant species in Alas Kedaton Tourism Forest. Meanwhile, the social population is all people in the Alas Kedaton Tourism Forest area. The sampling method for plant species is the quadratic method was used to investigate the diversity and the number of rare plants. While for the social sampling was conducted by interviewing with purposive sampling method to the local community around the Alas Kedaton areas. Determination of endangered plant species was conducted by studying of available documents, in-depth interviewing, and seeking information from various existent sources. The collected data analyzed descriptively. The results of this study indicated there are 48 species of plants with 26 families, which are generally found in Alas Kedaton Tourism Forest. Of this number, 42 (87.5%) plant species are included in the rare category; (2) of the 42 species of rare plants in the Alas Kedaton Tourism Forest, there are 8 (19.04%) plant species that are included in the National rare category, 20 (47.62%) rare plant species in Bali, 10 ( 23.81%) rare plant species in Tabanan Regency, and 4 (9.52%) species included in the rare category at the District level (especially Marga District); and (3) factors causing the scarcity of plant species in Alas Kedaton Tourism Forest are (a) past environmental degradation, (b) reproductive problems of rare plants, (c) human intervention, (4) disturbance by animals, especially long tailed monkeys ( Macaca fascicularis ) and bats ( Pteropus vampyrus ).